Vocabulary Teaching in Arabic Speaking Proficiency Class Arabic Literature Faculty of Cultural Sciences, Padjadjaran University - Ade Kosasih (Budapest International Research and Critics University, 2022)
Vocabulary is a very important language element to be taught to students in an effort to improve language skills, especially speaking skills. In teaching vocabulary, various strategies are used for maximum achievement. This article describes various vocabulary teaching strategies used in language proficiency classes. The data was obtained from the Arabic speaking proficiency class, namely in the form of several teaching materials used and the stages of learning. With the observation method and directly involved for one semester in the teaching process. The result is that the stages contained in the teaching materials are in line and even parallel with the ongoing learning stages. The results show that the process of teaching vocabulary takes place in an integrated manner with the stages of introducing new vocabulary, listening to conversational texts as the identification stage, then directed exercises. There are eight types of exercises, namely (1) wrong-true sentences; (2) compiling answers to questions; (3) synonyms; (4) antonyms; (5) complete the sentence with the appropriate word; (6) complete sentences with words that are already available; (7) arrange scattered words to make perfect sentences ; and (8) make sentences with the help of one word. Teaching with stages and exercises with various types significantly increases vocabulary mastery and increases the ability to speak.